Ekstraksi Astaxanthin Kulit Udang (Litopenaeus vannamei) Pantai Gunung Kidul Menggunakan Pelarut Minyak Bunga Matahari dan Etanol - Anik Prasetyaningsih; Graciela Carina Najoan; Abner Wisaksono; Djoko Rahardjo (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2021)
ABSTRACT As a maritime country with vast waters, Indonesia has many opportunities to utilize marine resources as a source of bioactive compounds that have the potential as active medicinal ingredients. One of the marine biotas that potentially contains the active compounds is the Vannamei shrimp's shell (Litopenaeus vannamei), which is commonly found as waste along the coast of Gunungkidul, Yogyakarta. The shrimp’s shell contains astaxanthin, a potential source of antioxidants for the health industry. The purpose of this study was to compare the astaxanthin extraction yield from L. vannamei shrimp shells using sunflower oil and 70% ethanol. The Astaxanthin extraction used sunflower oil and ethanol 70% as solvents and was done by maceration method, while the phytochemical test and Astaxanthin profiling used Thin Layer Chromatography and Spectrophotometer with Kelly and Harmon (1972) [5] calculations as well as pure Astaxanthin standards. The extraction yield of the 70% ethanol extraction was further processed by column chromatography using ether: ethanol (8: 2) as mobile phase. The highest Astaxanthin yield (220 mg / g of shrimp powder) was obtained from the extraction with sunflower oil compared to the 70% ethanol solvent, while the fractionation result with a chromatographic column from a crude extract of ethanol 70% showed high astaxanthin yield of 220.77 mg. / g fraction. The results of the fraction test on rat neutrophils, the best percentage reduction was at a concentration of 150 mg / g bw of rats.